Analisis Good Corperate Governance (GCG) Terhadap Kinerja Pengelolaan Dana Desa - Awotkay, Apolinaris S; Yulianti, Ni Luh Putu Nita; Richard, Yumiad Fernando; Bittikaka, Tiara Vallencia (EKONOMI & SOSIAL, 2023)
This research is to analyze Good Corporate Governance (GCG) on Village Fund Management Performance. This type of research uses quantitative methods. The sample in this study consisted of 30 respondents. Village Funds are a form of the state's commitment to protecting and empowering villages to become strong, advanced, independent and democratic. Kemangi Village, Tanah Miring District is one of the villages that received these funds. In the last 3-4 years these funds have no longer been used properly. The data analysis technique uses multiple linear regression analysis to test the research hypothesis. The findings in this research are: Transparency (X1) has a positive and insignificant effect on Village Fund Management Performance, Accountability (X2) has a positive and insignificant effect on Village Fund Management Performance, Accountability (X3) has no positive and insignificant effect on Fund Management Performance Village, Independence (X4) has a negative and insignificant effect on Village Fund Management Performance and Fairness (X5) shows that it partially has a positive and insignificant effect on Village Fund Management Performance. Meanwhile, the results of the F test show that transparency, accountability, accountability, independence and fairness have a positive and significant effect on Village Fund Management Performance.